Research and application prospects on key technologies of 50 Gbit/s front-haul modules - SHENG Xia; MA Tao; LIU Hao; FENG Jia (Dianxin kexue)
With the large-scale commercial use of the global 5G network and the rapid growth of mobile Internet traffic, more abundant wireless spectrum resources can be released, and the demand for high-speed optical modules in wireless front-haul networks is increasingly prominent. Focusing on the key technologies of 50 Gbit/s front-haul optical modules, two main networking methods were deeply analyzed, the typical transmission distance and link loss were analyzed, the maximum and minimum dispersion values of coarse wave division multiplexing (CWDM) wavelengths in a 10 km scenario were explored, and the corresponding dispersion compensation strategies were studied. Through experiments, the changes in optical power penalty of different multi-path interference (MPI) were verified, and the potential impact of MPI noise on error performance was analyzed in detail. In addition, deep research on the optoelectronic chip scheme of 50 Gbit/s modules was conducted, the parameters of various types of optical modules were rigorously tested, standardized suggestions for the optoelectronic interface parameters of 50 Gbit/s front-haul modules were proposed, the current standard status of 50 Gbit/s modules at home and abroad was detailed, and the development trend of future applications was prospected.